Mycobacterium smegmatis Induces Neurite Outgrowth and Differentiation in an Autophagy-Independent Manner in PC12 and C17.2 Cells - Feng, Xinwei; Lu, Junfeng; He, Zitian; Wang, Yidan; Qi, Fangfang; Pi, Rongbiao; Zhang, Ge (Frontiers in Cellular and Infection Microbiology, 2018)
Abstract: Both pathogenic and non-pathogenic Mycobacteria can induce the differentiation of immune cells into dendritic cells (DC) or DC-like cells. In addition, pathogenic Mycobacteria is found to stimulate cell differentiation in the nerves system. Whether non-pathogenic Mycobacteria interacts with nerve cells remains unknown. In this study, we found that co-incubation with fast-growing M. smegmatis induced neuron-like morphological changes of PC12 and C17.2 cells. Moreover, the M. smegmatis culture supernatant which was ultrafiltrated through a membrane with a 10 kDa cut-off, induced neurite outgrowth and differentiation in an autophagy-independent pathway in PC12 and C17.2 cells. Further analysis showed that IFN-γ production and activation of the PI3K-Akt signaling pathway were involved in the neural differentiation. In conclusion, our finding demonstrated that non-pathogenic M. smegmatis was able to promote neuronal differentiation by its extracellular proteins, which might provide a novel therapeutic strategy for the treatment of neurodegenerative disorders.